Atropine 0,01% combined with optic correction interventions on slowing childhood myopia progression: A Systematic Review and Meta-Analysis - Medina-Huayta, Mareyke (2024)
Introduction: Vision is critical in all aspects and stages of life. Myopia is the second cause of visual impairment worldwide and the prevalence of childhood myopia is increasing at an alarming rate, so a single treatment intervention is not sufficient and interventions that slow its progression should be combined. Objective: to determine the effect of atropine in 0.01% ophthalmic drops combined with optical correction interventions to slow the progression of childhood myopia. Methodology: a systematic review of articles published in PubMed, Embase, Cochrane Library, Ovid MEDLINE, Scopus, Web of Science, ScienceDirect, and EBSCOhost up to March 28, 2022, was performed. Meta-analysis was performed with a random-effects model by subgroups of interest. Results: eight studies were selected (six randomized clinical trials, one nonrandomized trial, and one cohort study), including a total of 632 children with low and medium myopia who used orthokeratology or monofocal contact lenses and atropine 0.01% eye drops. The meta-analysis showed results in favor of combined treatment to slow axial elongation by -0.15 mm with a 95% confidence interval (-0.23 to -0.07), high risk of bias, and high heterogeneity (I2=94%). Conclusions: according to the available evidence, atropine in 0.01% eye drops combined with mono-focal lenses or orthokeratology contact lenses could reduce axial elongation in children with low and medium myopia; however, the results are heterogeneous and the risk of bias is high.